OPTIMALISASI PERANGKAT DAN METODE IJTIHAD SEBAGAI UPAYA MODERNISASI HUKUM ISLAM (Studi Pemikiran Hassan Hanafi dalam Kitab Min an-Nash IlÄ al-WÄqiâ€™) - Imam Mustofa (Jurnal Hukum Islam, 2011)
This paper endeavors to explain the decline of Islam which is caused by stagnation of interpretation in its jurisprudence (fiqh), with no exertion in finding a new interpretation or understanding. To change the situation, we have to shift our paradigm to Islamic jurisprudence (fiqh) and principles of jurisprudence (usul al- fiqh) perceptions with a new understanding. Hassan Hanafi has contributed an excellent thought to reconstruct the stagnancy of Muslim world in order to modernize its jurisprudence with his writing, “Min an-Nash ilā al-Wāqi’”. In his article, Hanafi presented an innovative methodology in understanding the fiqh through integration between ra’yu and wahyu.